Edukasi Pemenuhan Nutrisi sebagai Upaya Pencegahan Stunting menggunakan Media Audio Visual - Winarningsih, Rahayu Arum; Juliani, Juliani; Syam, Verawati; Sitianingsih, Ayu; Saad, Aldini Safitri; Dirmayanti, Dirmayanti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Stunting is an irreversible growth disorder caused by a lack of nutritional intake during pregnancy (during 1,000 HPK), therefore, babies aged 0 to 2 years must receive balanced and optimal nutritional intake, because this period is the golden period of growth and development. child. Stunting is caused by a lack of understanding about how to overcome health problems (nutrition intake), therefore it is necessary to prevent stunting as an effort to increase health knowledge through education. Community service aims to find out how education about fulfilling nutrition in efforts to prevent stunting has an impact on increasing knowledge. The method of implementing counseling is carried out through face-to-face meetings and discussions which are considered more effective, where the activity begins with giving a pre-test questionnaire to measure the level of knowledge of mothers of toddlers, then the presentation of the material that takes place allows the audience to pay attention and focus on audio-visual videos regarding nutritional needs. To prevent stunting, evaluation of the results of the activity is carried out by administering a post-test questionnaire in the form of questions regarding the material that has been presented. This community service was carried out on September 18 2023 in Salekoe sub-district, East Wara sub-district, Palopo City, attended by 40 participants, all of whom were mothers of toddlers. The results showed that there was a significant influence on increasing respondents' knowledge before and after being given counseling with a p-value = 0.00 (p<0.05), where there were 20% of respondents who had good knowledge during the pre-test and this increased to 55% of respondents at the time of the post-test, 25% of respondents had sufficient knowledge about stunting at the time of the pre-test and this increased to 32.5% of respondents at the time of the post-test, 55% of respondents had insufficient knowledge at the time of the pre-test and decreased to 12.5% of respondents at the time post-test. The next follow-up is that health workers are expected to be able to use audio-visual videos in efforts to prevent stunting to increase knowledge among mothers of toddlers so that they can reduce the prevalence of stunting.